Project-Based Educational Development Management to Improve Teachers' Creative Skills Through a Differentiated Teaching Approach - Budi Tri Cahyono; Eka Budhi Santoso; Fatma Sukmawati; Relly Prihatin; Suparmi; Ratna Juwita (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to develop project-based education development management to improve teachers' creative skills through a differentiated teaching approach. The challenges of 21st-century education demand increased teachers' creative thinking skills, which are very important in teaching. This study involved 63 teachers from two high schools in Solo, Central Java, who were selected purposively. The research instrument was a descriptive test that measured teachers' creative thinking skills after receiving materials with the Differentiated Instruction approach. The development of this model used the 4D approach (Define, Design, Develop, Disseminate), which aims to ensure the validity, practicality, and effectiveness of the model's application. The results showed that applying a differentiated teaching approach significantly improved teachers' creative thinking skills compared to conventional teaching methods. This increase was more visible in the group of teachers with middle and upper ability categories, while in the lower ability category, no significant increase was found. These findings indicate that a differentiated teaching approach, combined with a project-based learning model and the 4D method, can effectively develop teachers' creative skills, so it is expected to improve the quality of teaching in schools.